2015
DOI: 10.1038/srep07658
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Single-photon level Memory for Polarization States

Abstract: An optical quantum memory is a stationary device that is capable of storing and recreating photonic qubits with a higher fidelity than any classical device. Thus far, these two requirements have been fulfilled for polarization qubits in systems based on cold atoms and cryogenically cooled crystals. Here, we report a room-temperature memory capable of storing arbitrary polarization qubits with a signal-to-background ratio higher than 1 and an average fidelity surpassing the classical benchmark for weak laser pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…That is to say, the memory stores just a single temporal mode, and a single temporal mode is retrieved from the memory [51]. This is clear from the structure of the solution (20), where the coherent mapping between input and output is described by the Green's function…”
Section: Mode Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, the memory stores just a single temporal mode, and a single temporal mode is retrieved from the memory [51]. This is clear from the structure of the solution (20), where the coherent mapping between input and output is described by the Green's function…”
Section: Mode Selectivitymentioning
confidence: 99%
“…An important class of memory protocol is based on stimulated twophoton transitions in a Λ-type atomic ensemble, where a bright control laser field couples the incident signal photons to a ground-state coherence in the atoms [17]. Memories based on electromagnetically-induced transparency (EIT) [18][19][20] and on far-off-resonant Raman absorption [21][22][23] both fall into this category, and in the following we will refer to all such memories as Λ-memories. Λ-memories in cold atoms have successfully stored single photons, but at room-temperature it was found that fluorescence noise [24] and four-wave mixing [25] became problematic.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason an alternate encoding is often used, such as the polarisation, orbital angular momentum, path, or arrival time (time-bin) of a single photon. Memories for polarisation qubits have been demonstrated using electromagnetically induced transparency (EIT) [11][12][13], atomic frequency comb (AFC) [14] memories, and Raman absorption [15]. EIT has also been used to store orbital angular momentum qubits with high fidelity [16].…”
mentioning
confidence: 99%
“…To be suitable for quantum applications, it is important that the coherence properties of the light are preserved during the storage process [24]. In particular, it is necessary to preserve the mutual coherence between two subsequently stored and retrieved pulses, as well as the second order autocorrelation function of the retrieved signal [7].…”
mentioning
confidence: 99%
“…Ten millisecond coherence times have been demonstrated in suitable cells [20], and advances up to 100 s are possible with improved antirelaxation coating technology [21], clearly sufficient for most applications. A variety of memory protocols for alkali vapors have been developed [22], based either on absorption engineering [23], or optically controlled light-matter interaction [24][25][26]. While wavelength matching to QD photons has been achieved [17,18,27], a remaining challenge for building a QD compatible atomic memory is that the required acceptance bandwith of δf ¼ 0.5 − 1.0 GHz [28,29] is rather large compared to the intrinsic linewidth of the alkali D lines, which is on the order of δ Rb ¼ 5 MHz [30].…”
mentioning
confidence: 99%